search
Log In
0 votes

The solution to the differential equation $\dfrac{d^2u}{dx^2}-k\dfrac{du}{dx}=0$  where $k$ is a constant, subjected to the
boundary conditions $u(0)$ = $0$ and $u(L)$ = $U$, is

  1. $u=U\dfrac{x}{L} $
  2. $u=U\left(\dfrac{1-e^{kx}}{1-e^{kL}}\right) $
  3. $u=U\left(\dfrac{1-e^{-kx}}{1-e^{-kL}}\right)$
  4. $u=U\left(\dfrac{1+e^{kx}}{1+e^{kL}}\right)$
in Differential Equations 1.4k points 4 7 17
recategorized by

Please log in or register to answer this question.

Answer:

Related questions

0 votes
0 answers
The differential equation $\dfrac{d^{2}y}{dx^{2}}+16y=0$ for $y(x)$ with the two boundary conditions $\dfrac{dy}{dx}\bigg \vert _{x=0}=1$ and $\dfrac{dy}{dx}\bigg \vert_{x=\displaystyle \frac{\pi}{2}}=-1$ has. No solution. Exactly two solutions. Exactly one solution. Infinitely many solutions.
asked Feb 27, 2017 in Differential Equations Arjun 24.6k points
0 votes
0 answers
The function $f(t)$ satisfies the differential equation $\dfrac{d^2f}{dt^2}+f=0$ and the auxiliary conditions, $f(0)=0$, $\dfrac{d(f)}{d(t)}(0)=4$. The Laplace transform of $f(t)$is given by $\dfrac{2}{s+1} \\$ $\dfrac{4}{s+1} \\$ $\dfrac{4}{s^2+1} \\$ $\dfrac{2}{s^4+1}$
asked Feb 19, 2017 in Differential Equations piyag476 1.4k points
0 votes
0 answers
The partial differential equation $\dfrac{\partial u }{\partial t}+u\dfrac{\partial u}{\partial x}=\dfrac{\partial^2 u}{\partial x^2}$ is a linear equation of order $2$ non-linear equation of order $1$ linear equation of order $1$ non-linear equation of order $2$
asked Feb 19, 2017 in Differential Equations piyag476 1.4k points
0 votes
1 answer
If the Laplace transform of a function $f(t)$ is given by $\frac{s+3}{\left ( s+1 \right )\left ( s+2 \right )}$, then $f(0)$ is $0$ $\frac{1}{2}$ $1$ $\frac{3}{2}$
asked Mar 1 in Differential Equations jothee 4.9k points
0 votes
0 answers
Consider the following differential equation $\left ( 1+y \right )\frac{dy}{dx}=y.$ The solution of the equation that satisfies condition $y(1)=1$ is $2ye^{y}=e^{x}+e$ $y^{2}e^{y}=e^{x}$ $ye^{y}=e^{x}$ $\left ( 1+y \right )e^{y}=2e^{x}$
asked Mar 1 in Differential Equations jothee 4.9k points
...